Evaluation of HRV/SPOT and TM/Landsat products for crop discrimination - Batista, Getúlio T.; Tardin, Antonio T.; Chen, Sherry C.; Dallemand, Jean F. (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this experiment was to evaluate SPOT and TM data for the discrimination of coffee (Coffea arabica L.), sugarcane (Saccharum officinarum L.), wheat (Triticum aestivum L.), and pasture (several species) in the northwest of Paraná State. Information on variety, planting date, phenological stage, plant height, row spacing and orientation, percent soil cover, etc. was collected in the field during the SPOT and TM data acquisitions (three SPOT and one Landsat scenes). Results showed that considering the four crops jointly, no identification difference was observed among the four products at the 95% significance level. However, for individual crop category there was a significant difference among the analyzed products. The results of digital analysis considering ali crop types jointly using SPOT or the three equivalent bands of TM were not statistically different at 95% level However, results obtained when replacing one of lhe visible bands of the TM by the middle infrared band 5 improved the classification results